Implementation of ‘Independent Campus-Freedom to Learn’ Policy - Tri Wintolo Apoko; Benny Hendriana; Isnaini Handayani; Isa Faqihuddin Hanif (Universitas Muhammadiyah Enrekang, 2022)
The policy of ‘Independent Campus-Freedom to Learn’ known as MBKM is currently participated by the students in Indonesia as it could provide the credit transfer of 20-60. This research aimed to investigate the students’ perceptions on the implementation of MBKM. The participants of this research were 98 students of Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta. The method used was a descriptive analysis design. The instrument used was a questionnaire completed by the students who already joined MBKM programs initiated either by the Ministry of Education, Culture, Research, and Technology or their study programs. The results showed that the students’ knowledge of MBKM policy was very good (92%) and their interests in MBKM program was also very good (98%). This research had some implications. The students’ involvements in MBKM programs increased and the capacity on the attitudes and skills also improved. Thus, this influences the sustainability of MBKM in the future.